STAD Type Cooperative Learning Model Assisted by Dakota Media Affects the Ability to Solve Mathematics Story Problems - Ni Putu Udyani; I Wayan Wiarta; Dewi Anzelina (International Journal of Elementary Education, 2024)
Most students experience difficulties in solving story problems in mathematics lessons, impacting learning outcomes that have not reached KKTP. This study aims to determine the significant influence of the STAD-type cooperative learning model assisted by dakota media on the ability to solve math story problems in grade V of elementary school. This study is an experimental research using a posttest-only control group design. The population of this study is 154 students. The sample was taken by cluster random sampling technique and a sample of the experimental class was obtained as many as 24 students and as a control class as many as 24 students. The data collection method is a test with an essay test instrument. The data from the study were analyzed by inferential statistical technique (t-test) polled variance. The results of the data analysis were obtained there is a significant influence of the STAD-type cooperative learning model assisted by the Dakota media on the ability to solve math story problems in grade V elementary school students. The implication of this research is that the STAD-type cooperative learning mode assisted by Dakota media can improve the ability to solve math story problems, active participation, interest, motivation, cooperation, creativity, and student learning outcomes, as well as create an innovative learning atmosphere that is in accordance with students' character.